2008
DOI: 10.1111/j.1528-1167.2007.01484.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early‐life LiCl‐Pilocarpine‐induced status epilepticus on memory and anxiety in adult rats are associated with mossy fiber sprouting and elevated CSF S100B protein

Abstract: SUMMARYPurpose: This study investigated putative correlations among behavioral changes and: (1) neuronal loss, (2) hippocampal mossy fiber sprouting, and (3) reactive astrogliosis in adult rats submitted to early-life LiCl-pilocarpine-induced status epilepticus (SE). Methods: Rats (P15) received LiCl (3 mEq/kg, i.p.) 12-18 h prior pilocarpine (60 mg/kg; s.c.). At adulthood, animals were submitted to behavioral tasks and after the completion of tasks biochemical and histological analysis were performed. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
21
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 44 publications
(50 reference statements)
8
21
1
1
Order By: Relevance
“…Two hours after SE onset, animals cycled through periods of forelimb clonus and periods of loss of the righting reflex with falling. All behavioural manifestations reported here for convulsive SE are in agreement with previous descriptions from Hirsch et al (1992) and de Oliveira et al (2008).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Two hours after SE onset, animals cycled through periods of forelimb clonus and periods of loss of the righting reflex with falling. All behavioural manifestations reported here for convulsive SE are in agreement with previous descriptions from Hirsch et al (1992) and de Oliveira et al (2008).…”
Section: Resultssupporting
confidence: 93%
“…Neurological disabilities observed in humans are very similar to those found in animal models of SE. Male rats that suffered SE at 16–20 days old showed long‐term deficits in spatial learning in the water maze task (Cilio et al, 2003) and showed an impairment in aversive memory learning in an inhibitory avoidance task (de Oliveira et al, 2008). Furthermore, animals submitted to LiCl‐pilocarpine‐induced SE between the 2nd and 3rd weeks of life presented increased levels of anxiety in the elevated plus maze, as well as impaired performance in the water maze task 3 months after the insult (Kubová et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of S100B protein is highly dependent on environmental factors including harmful stimuli. The overexpression of S100B protein during the epileptic process (especially in chronic epilepsy) suggests a principle role of S100B (Sakatani et al, 2007;de Oliveira et al, 2008). In the current study, we showed that S100B protein was increased with KA-induced epilepsy and this phenomenon was reversed by oral UR.…”
Section: Discussionmentioning
confidence: 50%
“…Although the direct link between hippocampal MF plasticity and anxiety-like behavior has not been reported, studies have shown a positive correlation between SP-MF sprouting and increased anxiety-like behavior in inbred (Prior et al ., 1997), as well as in outbred rats (de Oliveira et al ., 2008; Oztan et al ., 2011), suggesting that the MF system may contribute to modulation of anxiety-like responses. In support of this premise, our present data show that increased social anxiety-like behavior observed in HRs following a behaviorally sensitizing nicotine regimen is accompanied by increased SP-MF terminal field size, in comparison to saline pre-trained controls.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, data from inbred mice correlate heritable variance in MF size with different emotional behaviors, such as fear conditioning and anxiety-like behavior (Prior et al ., 1997). Likewise, studies on outbred rats show a positive correlation between MF sprouting and anxiety-like behavior in the light-dark box test (de Oliveira et al ., 2008), implicating MF plasticity in regulation of anxiety.…”
Section: Introductionmentioning
confidence: 87%